Simulation Of Muscle Loading In Two Activities With Finite Element Analysis - Bakar, Muhammad Haziq Abu (Universiti Sains Malaysia, 2017)
No doubt that muscle play important role in manipulating the strain distribution of the femoral bone. However, the significances are yet to be measured clearly in any literature. This study is conducted to determine the significances of muscles forces in walking and stairs climbing activities and establish which muscle (abductor, vastus lateralis or vastus medialis) is important in those activities. 3-D model of the femoral bone was constructed from CT datasets and appropriate loading conditions were subjected to it. The maximum and minimum strains at two regions of interest (femoral neck and femoral shaft) were recorded. The FE outcomes showed that, for walking activity, muscles activation (abductor and vastus lateralis) contributed to significant changes in strain distribution (95%, based on student t-test) in femoral neck region. In stairs climbing activity, contribution of muscles (abductor, vastus lateralis and medialis) is also notable in femoral neck region (95%, based on student t-test). Hence, muscles is indeed contributed significantly and required to be incorporated in the analysis.